Adsorbent Efficiency in Treating Phosphorus using Natural Treatment from Industrial Wastewater - A Review - Mohd Arshad, Nur Ain Nazirah; Hamdan, Rafidah (Penerbit UTHM, 2020)
Natural treatment are currently getting recognise as remedies in wastewater treatment for small industries. Natural treatment equipped with natural, man-made and by-products materials coming from various sources such as agricultural wastes, household and industrial sectors are commonly being used. Its availability is abundant and simultaneously contributing to waste recovery, reuse and minimization. Its abilities to remove pollutants such as phosphorus are promising since multiple researches have been done to provide a new insight in treating pollutant with natural, man-made and by-products adsorbent. Examples of the three types of adsorbent that have been studied are red mud, soy bean, eggshells, dates, steel slag and many more. Despite countless reviews have been made in the last few years, a direct comparison on different adsorbent along with its efficiency in treating industrial wastewater is unsatisfactory and lacking since most of the studies are using synthetic solution which under controlled condition. The application of the treatment is unfavourable due to limited understanding of phosphorus removal. Thus, the aim of the study was to revise the current literature regarding natural adsorbent efficiencies and its application towards industrial wastewater including the adsorbent characteristics and methods of phosphate removal involves.